Implementation and Application of Functional Languages 24th International Symposium, IFL 2012, Oxford, UK, August 30 - September 1, 2012, Revised Selected Papers - Hinze, Ralf.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book contains the selected peer-reviewed and revised papers from the 24th International Symposium on Implementation and Application of Functional Languages, IFL 2012, held in Oxford, UK, in August/September 2012. The 14 papers included in this volume were carefully reviewed and selected from 28 revised submissions received from originally 37 presentations at the conference. The papers relate to the implementation and application of functional languages and function-based programming.
A Notation for Comonads -- Iterating Skeletons -- Structured Parallelism by Composition -- Building JavaScript Applications with Haskell -- Advances in Lazy SmallCheck -- OCaml-Java: from OCaml sources to Java bytecodes -- The HERMIT in the Tree: Mechanizing Program Transformations in the GHC Core Language -- Optimisation of Generic Programs through Inlining -- A Type-and Control-Flow Analysis for System F -- Dependently-typed Programming in Scientific Computing: Examples from economic modelling -- Engineering Proof by Reflection in Agda -- Agda Meets Accelerate -- An Embedded Type Debugger -- Pure and Lazy Lambda Mining: An Experience Report -- Decomposing Metaheuristic Operations.
Keywords: Computer science; Software engineering; Logic design; Computer Science; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Software Engineering; Mathematical Logic and Formal Languages; Programming Techniques; Information Systems Applications (incl. Internet).